A cruzada das crianças : um estudo de caso sobre as condições sociais de infância na contemporaneidade - Facci, Douglas Tadeu da Silva (2013)
This text contains the results of research performed in master, whose central goal was to investigate the social conditions of childhood, problematizing the issue of experience of life and of the child's autonomy in contemporaneity. The object of this study can be explained as being the experience of childhood among children pre-adolescent students in a public school, in the town of Maringa, Parana, and through which it sought an empirical approach and a theoretical reflection of conditions of childhood in contemporary times. This study is, in part, in the selection, coordination and presentation of a dense empirical material, generated in a field work with children in a class of fifth-series, whose age range is situated, predominantly, between 10 to 12 years, although some, being exceedingly, beyond this age. Through a study of ethnographic nature it was obtained a vast quantity and diversity of information regarding the living conditions of children, both in its subjective dimension (psychological) and social. Thus, this research is, also, in an effort theoretical, sociological, anthropological, reflexive, in contextualizing, analyze, interpret (in the sense of understanding) and to reconstitute this material, and thus do emerge from these experiences of childhood, in addition to its phenomenological manifestation and fragmented. In this we must exercise dialectic between the conditions of existing stocks of children involved in the research and the theoretical reflection to respect, reported to the theoretical-methodological assumptions of the new Sociology of Childhood, which gains prominence in the academic field with a new approach of childhood, while a generational category, and the child as a social actor, involved in active form in the processes of their social formation. Adopted the ethnographic case study format as methodological research, from a theoretical positioning resulting from an intersection paradigmatic, designated interpretativismo critical. It can be concluded, from the empirical material and the light of the selected critical bibliography, that contemporary society denies the necessary conditions for a social statement of the child, denies his effective autonomy through social processes that deflate the childhood and the sociability necessary to the development of a full social individuality.